Упростить выражение срочно

0 голосов
30 просмотров

Упростить выражение срочно


image

Математика (377 баллов) | 30 просмотров
0

Качество не очень...

Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:

\left( \frac{a^4 - 2a^2b+4b^2}{a^6+8b^3} + \frac{a^2-2b}{a^4-4b^2}\right) \cdot (a^2 + 2b) = (\frac{a^4 - 2a^2b+4b^2}{(a^2+2b)(a^4 - 2a^2b+4b^2)} + \frac{(a^2-2b)}{(a^2+2b)(a^2-2b)}) \cdot (a^2+2b) = \frac{2 \cdot (a^2+2b)}{(a^2+2b)} = 2
(430 баллов)
0 голосов

(a^4-2a²b+4b²)/(a²+2b)(a^4-2a²b+4b²)+(a²-2b)(a²-2b)(a²+2b)=
=1/(a²+2b)+1/(a²+2b)=2/(a²+2b)

2/(a²+2b)*(a²+2b)=2

(750k баллов)